The Effect of Deferred Taxes, Dividend Payout, And Environmental Management Accounting on Company Financial Performance (Consumer Non-Cyclical Sector Companies Listed on the Indonesian Stock Exchange 2018-2022) - Putri, Risky Amelia; Barli, Harry (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This research aims to investigate the effect of deferred taxes, dividend payout, and environmental management accounting on company financial performance. This type of research uses quantitative methods with an associative approach, the research population is the Consumer Non-Cyclicals sector in 2018-2022. The sampling technique used purposive sampling which was tested using descriptive statistical analysis of the e-views 9 application. The results of the study showed that deferred tax, dividend payout, and environmental management accounting simultaneously had an effect on the company's financial performance, deferred tax had no effect on the company's financial performance, dividends payout has no effect on the company's financial performance, and environmental management accounting has an effect on the company's financial performance.